COMPARISON OF METOCLOPRAMIDE, PROCHLORPERAZINE AND PLACEBO IN PREVENTION OF POSTOPERATIVE NAUSEA AND VOMITING (PONV) FOLLOWING TONSILLECTOMY IN YOUNG ADULTS - Jamil, Muhammad; Gilani, Syed Mushtaq; Khan, Shamsher Ali (Journal of Ayub Medical College Abbottabad, 2005)
Background: Postoperative nausea and vomiting following anaesthesia and surgery are common and can create considerable problems regarding management of patients and outcome of the surgical procedure. Methods: This study evaluates and compares the efficacy and safety of the metochlopramide to that of prochlorperazine in the prevention of postoperative nausea and vomiting after tonsillectomy in young adult patients. 150 patients, of either sex, undergoing tonsillectomy under the same anaesthetic technique were studied in a randomized, double blind, placebo controlled manner. Either metoclopramide 0.1-0.2 mg kg-1, prochlorperazine 0.1-0.2 mg kg -1 or 5% Dextose and normal saline (5% D/N.S) (2ml) as placebo was injected intravenously 10 minutes before induction of general anaesthesia. Episodes of nausea, retching/ vomiting, adverse events, vital signs, the need for rescue antiemetic drug ( metoclopramide 0.1-0.2 mg kg-1 IV) were recorded until four hours from the end of the surgical procedure. Results: The overall frequency of PONV was 18%, 16%, and 24% in group A (metoclopramide), B (prochlorperazine) and C (placebo) respectively. The need for rescue antiemetic was 2%, 8% and 12% in Prochloperazine group, metoclopramide group and control group respectively. These differences did not reach statistical significance (P>0.05). During the study period 82%, 84% and 76% of patients in group A, B and C respectively were found free from postoperative nausea and vomiting, and no adverse events related to either of the test medication were noted in any patient. Conclusion: It is concluded that the differences in the results of occurrence of PONV in the experimental group and control group are not statistically significant. However either Prochloperazine 0.1 - 0.2 mg kg-1 or metoclopramide 0.1 - 0.2 mg kg-1 can be safely administered as Prophylactic antiemetic till the availability of more efficacious and safe antiemetic drugs. Keywords: Postoperative nausea and vomiting (PONV), metoclopramide, prochlorperazine, tonsillectomy.